Integrated 16S rDNA-Seq and metabolomics reveal seasonal dynamics of gut microbial–SCFA–immune crosstalk in diarrheic calves - Wang, Qianqian; Lu, Qicheng; Tang, Yaqin; Li, Qiuyan; Gao, Peiyun; Pang, Shaoyang; Zhang, Wenju; Nie, Cunxi; Niu, Junli; Ma, Xiaoling (Frontiers in Veterinary Science, 2025)
IntroductionNeonatal calf diarrhea incidence varies seasonally, increasing during climatic fluctuations. This study investigated body weight and size, immune function, intestinal permeability, rectal microbiota, and short-chain fatty acid (SCFA) levels in diarrheal and healthy lactating calves across seasons.MethodsTen lactating healthy and ten diarrhea calves were selected in each season, blood and rectal contents samples were collected. Serum immunity, cytokines, and intestinal permeability markers were measured using kits. Rectal microbiota composition was analyzed via 16S rDNA amplicon sequencing, and SCFA profiles of rectal contents were characterized using targeted metabolomics.ResultsSignificantly higher levels of interleukin-1β (IL-1β), endotoxin (ET), and diamine oxidase (DAO) and lower levels of interleukin-10 (IL-10), immunoglobulin (IgA and IgG) levels were observed in diarrheic calves compared to those of healthy controls across all four seasons. Acetate and valeric acid concentrations were significantly lower in diarrheic calves in summer, autumn, and winter. In addition, diarrheic calves exhibited significantly reduced alpha diversity compared to than that of healthy controls, as indicated by lower Chao1, Observed_features, and Shannon indices. The relative abundances of Escherichia-Shigella, Fusobacterium, and Peptostreptococcus in the diarrheal calf group were significantly higher, while Faecalibacterium and Bifidobacterium were significantly lower. Clostridium_sensu_stricto_1 content was positively correlated with ET and DAO and negatively correlated with IL-10 and IgA. Escherichia-Shigella was positively correlated with ET, DAO, IL-1β, and TNF-α, but negatively correlated with IL-10 and IgA. Fusobacterium was positively correlated with ET, DAO, and IL-1β.DiscussionIn conclusion, seasonal factors have an influence on the indicators related to diarrhea in calves. Diarrheic lactating calves showed the characteristics of reduced immunity, increased inflammatory response, reduced rectal microbial diversity, and altered microbiota profiles and SCFA content, and these alterations were closely related to the occurrence of diarrhea in calves.